The addition of retorted oil shale increases carbon retention of plant residues in the soil - Leão, Ricardo Elso; Giacomini, Sandro José; Redin, Marciel; Souza, Eduardo Lorensi; Silveira, Carlos Augusto Posser (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the short‑term and the residual effect of retorted oil shale (ROS) rates on the C retention of crop residues in the soil. The mineralization and C retention of soybean leaves and stems enriched with 13C were evaluated, in soil with and without history of ROS application and in the presence and absence of increasing ROS rates. There was a short‑term effect of ROS on C retention in the soil. This effect only occurred with the mixture of leaves + 3 Mg ha‑1 ROS, in which C retention in the soil surpassed by 21% the one observed with the sole application of leaves. ROS has the potential to retain C in the soil.